2009
DOI: 10.1159/000201943
|View full text |Cite
|
Sign up to set email alerts
|

Nimustine (ACNU) Plus Teniposide (VM26) in Recurrent Glioblastoma

Abstract: Background: In a previous trial (NOA-01), the combination of nimustine and teniposide showed efficacy in previously untreated glioblastoma (GBM). After establishing temozolomide as standard first-line therapy in GBM patients, the nimustine (ACNU)/teniposide (VM-26) combination has been employed as salvage chemotherapy for recurrent GBM. However, data on the toxicity and efficacy of this regimen in recurrent GBM are lacking. Patients and Methods: In two neurooncological centers, all patients with recurrent GBM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…After failure of temozolomide (TMZ), there is no established standard salvage chemotherapy. Nitrosourea compounds such as BCNU, ACNU or CCNU are widely used but have limited efficacy [6 months’ progression-free survival (PFS-6) rates of 19–29%] [2,3,4] and considerable toxicity. Also, salvage therapy with bevacizumab has shown some efficacy in phase II trials [5] but these data have not been sufficient to approve bevacizumab for general use and reimbursement in Europe in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…After failure of temozolomide (TMZ), there is no established standard salvage chemotherapy. Nitrosourea compounds such as BCNU, ACNU or CCNU are widely used but have limited efficacy [6 months’ progression-free survival (PFS-6) rates of 19–29%] [2,3,4] and considerable toxicity. Also, salvage therapy with bevacizumab has shown some efficacy in phase II trials [5] but these data have not been sufficient to approve bevacizumab for general use and reimbursement in Europe in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Although comparisons with other trials and retrospective case series may not be legitimate, this contrasts with the experience with BCNU monotherapy (PFS-6: 17.5%) [15] or procarbacine, BCNU, and vincristine chemotherapy (42%) [17] in chemotherapy-naive GBM patients. More importantly, retrospective series with ACNU/VM26 therapy (PFS-6: 19-29%) [12,13], including heavily pretreated patients, and prospective series with CCNU monotherapy (PFS-6: 13-25%) [11,18], including TMZ-pretreated patients, had a higher PFS-6 than BCNU/VM26 therapy in our retrospective series. To explain the differences between the different series, it has to be taken into account that most patients included in our series received BCNU/VM26 as third- or fourth-line therapy or even later in the course of the disease.…”
Section: Discussionmentioning
confidence: 76%
“…Also, nitrosoureas such as carmustine (BCNU), lomustine (CCNU), and nimustine (ACNU) have been commonly used for decades in recurrent cases with some efficacy; in a randomized trial using CCNU as the standard arm, a PFS-6 of 19% was found [11]. ACNU alone or in combination with teniposide (VM26) showed a PFS-6 of 19-29% in retrospective case series [12,13]. When ACNU was no longer available in Europe, the Neurooncology Center at the University of Bonn switched from intravenous ACNU to intravenous BCNU application.…”
Section: Introductionmentioning
confidence: 99%
“…Before chemotherapy, mean leukocyte and thrombocyte counts were similar in the cohorts (leukocyte counts: 6.34 9 10 3 /mm 3 . Leukocyte and thrombocyte counts dropped after chemotherapy in both cohorts, but the relative decrease of leukocyte counts was less pronounced in cohort B compared with cohort A during both periods (p=0.02 and p=0.005, respectively, Figure 2A).…”
Section: Toxicity Analysismentioning
confidence: 87%
“…3,4 Indeed, teniposide and nitrosoureas are two cytostatic drugs that both induce predominantly hematotoxic adverse effects. Teniposide (VM26) is a podophyllotoxin derivate that prevents cell replication by inhibiting the activity of topoisomerase II.…”
mentioning
confidence: 99%